A comprehensive obstacle analysis framework on dispersed wind power: A case of China. (15th May 2021) - Wu, Yunna; Liu, Fangtong; Deng, Zhongqing; He, Jiaming; Xu, Chuanbo; Tao, Yao; Ke, Yiming
Abstract: Dispersed wind power is undoubtedly assisting sustainable development of society but hindered by various factors. To promote the development of dispersed wind power, this paper is devoted to obstacles identification and analysis to provide effective development proposals. Firstly, a three-stage process (namely collection, screening and improvement) is developed to extract common obstacles from literature and explore unique obstacles according to the characteristics and development status of dispersed wind power. Then, DANP method is improved to analyze interaction, interrelation and relative importance among filtered obstacles, where Pythagorean fuzzy numbers and K-Means clustering algorithm are introduced to modify incomplete information collection and arbitrary threshold determination, respectively. Three reasonable thresholds are determined according to clustering results, which divide the influence degree among obstacles into four categories (namely, high, moderate, low and no influence). The analysis results indicate that lagged unified planning ranks the first of obstacles, followed by financial difficulty and restricted grid access. On that basis, some practical proposals on regional coordinated development are suggested, including building unified coordination platforms and forming dispersed wind power project group. This paper does not only enrich material database for scholars, but also provide reference and guidance for government and related enterprises. Highlights: Twelve obstacle factors are identified for the development of dispersed wind power in China. Pythagorean fuzzy numbers is introduced in DANP to increase the flexibility of decision makers' evaluation. K-Means cluster algorithm is applied to determine thresholds of different influence degrees for further in-depth analysis. A series of proposals on regional coordinated development for dispersed wind power are put forward.